2015
DOI: 10.1108/amhid-02-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Home visits: a reflection on family contact in a specialist forensic intellectual disability service

Abstract: Purpose – There is little published literature about the number of home visits provided to patients within forensic intellectual disability units, and there is no published data on variables that affect home visits. There is a need for a baseline audit that can formulate standards for future practice. The paper aims to discuss these issues. Design/methodology/approach – This paper describes the home visit programme within a forensic intellectual disability service, and a baseline audit of the programme. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Four studies investigated aspects of the patient experience within forensic in-patient services. 21 , 23 , 59 , 129 A systematic review and Delphi study 21 identified patient and carer experience as an important indicator of service quality within in-patient forensic services for people with intellectual disabilities and/or autism. Three studies, excluding the systematic review by Morrissey et al, 21 investigated patient experience within in-patient forensic services, 23 , 59 , 129 with one focusing specifically on family and home visits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies investigated aspects of the patient experience within forensic in-patient services. 21 , 23 , 59 , 129 A systematic review and Delphi study 21 identified patient and carer experience as an important indicator of service quality within in-patient forensic services for people with intellectual disabilities and/or autism. Three studies, excluding the systematic review by Morrissey et al, 21 investigated patient experience within in-patient forensic services, 23 , 59 , 129 with one focusing specifically on family and home visits.…”
Section: Resultsmentioning
confidence: 99%
“… 21 , 23 , 59 , 129 A systematic review and Delphi study 21 identified patient and carer experience as an important indicator of service quality within in-patient forensic services for people with intellectual disabilities and/or autism. Three studies, excluding the systematic review by Morrissey et al, 21 investigated patient experience within in-patient forensic services, 23 , 59 , 129 with one focusing specifically on family and home visits. 129 Two papers made use of semi-structured interviews and identified hospital admission as ‘helpful’, although the environment was characterised as ‘noisy’ and ‘stressful’, with both studies recognising loss of freedoms and restrictions of personal items as challenging for patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, only family carers actively in touch with their relative and engaged with services could be approached. Previous research has reported that approximately 20% of patients in FIDD services are not in any contact with relatives (Cheshire et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Relationships are important to the wellbeing of individuals’, including those with neurodevelopmental and mental disorders (Bishop-Fitzpatrick et al, 2017; Kilroy et al, 2014). However, challenges arise for people within this population due to the lack of opportunities to develop such relationships (Cheshire et al, 2015; Chinn et al, 2011).…”
Section: Discussionmentioning
confidence: 99%